2013
DOI: 10.1002/jbm.b.32896
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of mechanical properties of experimental composite by Fuller's earth nanofibers for cervical restoration

Abstract: In this research, we studied improvement of mechanical properties of dimethacrylate-silica based dental composites by addition of Fuller's Earth (FE) clay. Three composites were made as base compounds consisting of 68, 58, and 48 wt % resin and 31, 41, and 51 wt % silica, respectively. Afterward, the composites were modified by adding FE. Mechanical properties including flexural strength, flexural modulus, work-of-fracture, fracture toughness, and microhardness were measured. Clay particles and fracture surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Although the stress-induced phase transformation of zirconia contributes to the toughening effect, the authors also attributed this increase in FT to the incorporation of ZS nanofibers, which play the role of a “bridge” in the fracture regions [32] . Other studies also reported that the FT of resin-based composites is improved when they are reinforced with fibers [25] , [29] , [30] , [40] , [41] , [42] .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Although the stress-induced phase transformation of zirconia contributes to the toughening effect, the authors also attributed this increase in FT to the incorporation of ZS nanofibers, which play the role of a “bridge” in the fracture regions [32] . Other studies also reported that the FT of resin-based composites is improved when they are reinforced with fibers [25] , [29] , [30] , [40] , [41] , [42] .…”
Section: Discussionmentioning
confidence: 90%
“…There are different compositions of glass fibers, such as S-glass or E-glass, representing different properties, although all of them are amorphous and atoms arranged randomly. Overall, glass fibers-reinforced composites provide high toughness, non-corrosiveness and aesthetic characteristics [24] , [29] , [30] , [40] , [42] , [43] , [45] , [47] , [48] , [49] , [50] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical investigations showed that for 0.72 wt.% of nanofiller, the properties were the best, with a flexural strength of 105 MPa, flexural modulus of 2.79 GPa and a work-of-fracture (WOF) 8.19 kJ/m 2 , which is very important for cervical restorations. In comparison with the composite without filler, these values slightly increased [ 47 ]. However, clay substances can insignificantly affect some mechanical properties of the dental composite, as described by Mucci et al The authors introduced a polymer montmorillonite (MMT), which is composed of sheets of approximately 1 nm thickness and a diameter in the range of 50 nm to a few µm.…”
Section: Restorative Dentistry (Dental Materials)mentioning
confidence: 99%